2022
DOI: 10.1101/2022.11.28.22282808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and outcomes of patients with COVID-19 at high-risk of disease progression receiving sotrovimab, oral antivirals or no treatment in England

Abstract: Introduction: There is limited real-world evidence surrounding the effectiveness of early, mild-to-moderate COVID-19 treatments following the emergence and dominance of Omicron SARS-CoV-2 subvariants. Here, characteristics and acute clinical outcomes are described for patients with COVID-19 treated with sotrovimab, nirmatrelvir/ritonavir or molnupiravir, or patients at highest risk per NHS criteria but who were untreated. Methods: Retrospective cohort study of non-hospitalised patients who received early treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(69 citation statements)
references
References 24 publications
2
66
1
Order By: Relevance
“…Those which have studied similar cohorts, including one peer-reviewed and one pre-print study exploring the UK’s targeted deployment, also reported lower rates of hospital admission and death amongst those receiving treatment. 26,27 Whilst in contrast to the findings of our secondary analysis, Zheny et al reported sotrovimab treatment was associated with a reduced risk of death or hospitalisation within 28 days of a positive COVID-19 test when compared with molnupiravir, neither that study nor the pre-print study conducted by Patel et al, were designed to compare the effectiveness of treatment to no treatment, in the high-risk cohort.…”
Section: Discussioncontrasting
confidence: 66%
“…Those which have studied similar cohorts, including one peer-reviewed and one pre-print study exploring the UK’s targeted deployment, also reported lower rates of hospital admission and death amongst those receiving treatment. 26,27 Whilst in contrast to the findings of our secondary analysis, Zheny et al reported sotrovimab treatment was associated with a reduced risk of death or hospitalisation within 28 days of a positive COVID-19 test when compared with molnupiravir, neither that study nor the pre-print study conducted by Patel et al, were designed to compare the effectiveness of treatment to no treatment, in the high-risk cohort.…”
Section: Discussioncontrasting
confidence: 66%
“…Nonetheless, our results are consistent with those from a recent study, conducted between 16 th December 2021 and 10 th February 2022 using the OpenSAFELY-TPP platform, which reported that 0.96% of patients confirmed to have been treated with sotrovimab had a COVID-19-attributable hospitalisation or death within 28 days of treatment [14]; in our study, 1.0% of patients who were assumed to have been treated with sotrovimab experienced a COVID-19-attributable hospitalisation in the 28-day post-treatment acute period. The results are also similar to those of another recently completed analysis that used data from the Discover database in North-West London, which reported 0.7% of people confirmed to have been treated with sotrovimab experiencing a COVID-19-attributable hospitalisation during the 28 days following treatment (study period was 1 st December 2021 – 31 st May 2022 with subvariants predominance as follows: Omicron BA.1 from 1 st December 2021 – 28 th February 2022 and Omicron BA.2 from 1 st March 2022 – 31 st May 2022) [15]. Similarly, our findings of low rates of COVID-19-attributable deaths and hospitalisations in patients with advanced kidney disease are consistent with a those from a recent study in non-hospitalised patients with COVID-19 on kidney replacement therapy; treatment with sotrovimab resulted in a substantially lower risk of severe COVID-19 outcomes compared with molnupiravir during periods of Omicron BA.1 through to BA.5 subvariant dominance [16].…”
Section: Discussionmentioning
confidence: 99%
“…The following are the results of the meta-analyses conducted by the evaluated outcome. Three studies reported subgroup data by vaccination status (11,14,18) and four other studies reported data by age group (14,18,19,24). In the analysis by vaccination status, nirmatrelvir-ritonavir reduced the risk of mortality both in the unvaccinated group (OR=0.41; 95% CI: 0.29-0.58) and in the vaccinated group (OR=0.31; 95% CI: 0.14-0.68), with no significant difference between the groups (Fig 3A).…”
Section: Effectiveness Outcomesmentioning
confidence: 99%
“…The sixteen studies finally considered were conducted in 5 countries (Canada, China, United States, Israel, and United Kingdom). Of these, as of the last update of the search, 12 studies were published (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and 4 were unpublished studies (preprint) (23)(24)(25)(26). All studies were retrospective cohorts of data obtained from electronic records of hospitals and other healthcare centers, collected from January 2021 to October 2022.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation